Analisis Transformasi Digital terhadap Kinerja Perusahaan dengan Inovasi Digital Sebagai Variabel Mediasi (Studi Kasus Program CPMS pada Kontraktor Ciputra Group) - Panggayuh, Caesilia Ageng Raras; Krisprimandoyo, D Agung (IPM2KPE, 2024)
This study aims to investigate the impact of digital transformation on company performance by using digital innovation as a mediating variable, especially in the context of users of the Contract & Procurement Management System (CPMS) application among Ciputra Group contractors. This study adopts a quantitative approach based on the Theory of Diffusion of Innovation by Everett M. Rogers. The questionnaire was distributed to 73 external CPMS user respondents via Google Form. Data analysis was carried out using regression analysis for mediating variables and path analysis with SPSS 27.0, comparing the direct effect of digital transformation (variable X) on company performance (variable Y) and the indirect effect by including digital innovation (variable M) as a mediator. The results showed that there was no significant direct effect between digital transformation and company performance. However, there was a significant indirect effect through digital innovation. This shows the important role of digital innovation as a mediator that supports improving company performance. In conclusion, through the CPMS application, digital transformation can improve company performance by increasing work effectiveness and accelerating the financing process. This study suggests the need for further research to explore more complex and broader aspects of the impact of digital transformation. Keywords: Digital Innovation, Company Performance, Digital Transformation